2021
DOI: 10.1038/s41598-021-87514-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid weight loss in free ranging pygmy killer whales (Feresa attenuata) and the implications for anthropogenic disturbance of odontocetes

Abstract: Understanding the impacts of foraging disruptions to odontocete body condition is fundamental to quantifying biological effects of human disturbance and environmental changes on cetacean populations. Here, reductions in body volume of free-ranging pygmy killer whales (Feresa attenuata) were calculated using repeated measurements of the same individuals obtained through Unoccupied Aerial System (UAS)-photogrammetry during a prolonged disruption in foraging activity arising from a 21-day stranding event. Strande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…They also provide information on the physical and biological environment that can characterise the prey landscape ( Arranz et al, 2011 ; Goulet et al, 2019 ; McMahon et al, 2019 , 2021 ). Unmanned systems are currently being applied to marine mammal bioenergetics, particularly the use of aerial systems to estimate body condition and growth ( Fearnbach et al, 2018 ; Lemos et al, 2020 ; Aoki et al, 2021 ; Currie et al, 2021 ; Shero et al, 2021 ; Stewart et al, 2021a ; Christiansen et al, 2022 ), and surface and underwater systems to survey prey communities ( Kuhn et al, 2019 ; Benoit-Bird et al, 2020 ). Environmental DNA (eDNA) is a promising emerging tool for addressing questions related to prey landscapes, as it appears able to characterise the distribution and diversity of prey communities ( Visser et al, 2021 ) as well as prey biomass ( Rourke et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…They also provide information on the physical and biological environment that can characterise the prey landscape ( Arranz et al, 2011 ; Goulet et al, 2019 ; McMahon et al, 2019 , 2021 ). Unmanned systems are currently being applied to marine mammal bioenergetics, particularly the use of aerial systems to estimate body condition and growth ( Fearnbach et al, 2018 ; Lemos et al, 2020 ; Aoki et al, 2021 ; Currie et al, 2021 ; Shero et al, 2021 ; Stewart et al, 2021a ; Christiansen et al, 2022 ), and surface and underwater systems to survey prey communities ( Kuhn et al, 2019 ; Benoit-Bird et al, 2020 ). Environmental DNA (eDNA) is a promising emerging tool for addressing questions related to prey landscapes, as it appears able to characterise the distribution and diversity of prey communities ( Visser et al, 2021 ) as well as prey biomass ( Rourke et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prior measures of AA and AI from biopsies collected from southern hemisphere humpback whales demonstrated that it was possible to identify fasting and feeding groups in one study (Castrillon et al, 2017) and sex ratios were correlated with blubber biopsy AA measures in another (Druskat Frontiers in Physiology frontiersin.org et al, 2019). To our knowledge, AA and AI have not yet been compared in blubber of biopsied odontocetes although AA and AI values were consistent with drone derived body condition assessments in a limited number of pygmy killer whales involved in a prolonged mass stranding event (Currie et al, 2021). Measurement of blubber AA and AI in biopsies has the potential to serve as a valuable tool for conducting overall body condition assessments in odontocetes.…”
Section: Applicationmentioning
confidence: 87%
“…The relationship between body condition and provisioned energy has not been investigated for any odontocete, since it is usually impractical to confirm milk delivery or estimate volume ( Gero and Whitehead, 2007 ). However, aerial photogrammetry has recently been used successfully to quantify changes in body condition during foraging interruption for odontocetes ( Currie et al , 2021 ) and assess how female body condition drives calf development in baleen whales ( Christiansen et al , 2016 , 2018 ). Similar data on calf development and maternal condition could be collected for odontocetes, ideally under both natural and disturbed conditions.…”
Section: Discussionmentioning
confidence: 99%